2000
DOI: 10.1007/s004250050683
|View full text |Cite
|
Sign up to set email alerts
|

Drought induces fructan synthesis and 1-SST (sucrose: sucrose fructosyltransferase) in roots and leaves of chicory seedlings ( Cichorium intybus L.)

Abstract: Seeds of Cichorium intybus L. var. foliosum cv. Flash were sown in acid-washed vermiculite and grown in a controlled-environment growth chamber. After 1 month of growth, plantlets did not contain sucrose:sucrose 1-fructosyltransferase (1-SST), the key enzyme in fructan biosynthesis. No fructan could be observed. Some of the plants were submitted to drought for 2 weeks. Glucose, fructose and sucrose concentrations increased in roots and leaves of stressed plants and the fructan concentration in roots and leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 35 publications
6
72
1
9
Order By: Relevance
“…For enzyme activity measurements, representative samples of ®eld-grown sugar beet plants (roots, petioles and leaves without the major vein) were collected weekly between June 21 and October 5, and samples were stored at À808C for later analysis. Sugar beet seedlings and young plants were also grown in a controlled growth chamber as described by De Roover et al (2000). A number of 6-day-old seedlings and 1-month-old plants were harvested.…”
Section: Plant Materialsmentioning
confidence: 99%
“…For enzyme activity measurements, representative samples of ®eld-grown sugar beet plants (roots, petioles and leaves without the major vein) were collected weekly between June 21 and October 5, and samples were stored at À808C for later analysis. Sugar beet seedlings and young plants were also grown in a controlled growth chamber as described by De Roover et al (2000). A number of 6-day-old seedlings and 1-month-old plants were harvested.…”
Section: Plant Materialsmentioning
confidence: 99%
“…This happens when the photosynthetic capacity of the leaves becomes higher than what is needed for leaf growth and maintenance. De Roover et al [75] demonstrated that 1-SST activity and fructan biosynthesis are initiated when growth of chicory seedlings is arrested by drought. Direct proof of the involvement of sucrose in fructan biosynthetic gene induction comes from incubation of detached leaves in sucrose solutions [36,76], resulting in fructan biosynthesis.…”
Section: Regulation Of Fructan Metabolismmentioning
confidence: 99%
“…The main storage sites of fructans in grasses are the leaf sheath and, to a lesser extent, the leaf base (Housley and Volenec, 1988;MorvanBertrand et al, 2001;Morvan et al, 1997;Roth et al, 1997;Volenec, 1986). Fructans have been implicated in conferring tolerance to drought and cold stress (De Roover et al, 2000;Housley and Pollock, 1993;Pilon-Smits et al, 1995;Thomas and James, 1999;Volaire and Lelievre, 1997). Their synthesis occurs de novo in carbohydrate accumulating tissue, with sucrose as the major or sole precursor (Cairns and Pollock, 1988a;Cairns et al, 1999;Wagner et al, 1983).…”
Section: Introductionmentioning
confidence: 99%